Prevalence and characteristics of resistant staphylococcus aureus in hospital environment. - De Silva, N (My University, 1993)
One hundred and seventy one strains of Staphylococcus aureus were isolated from specimens processed in the laboratory of the department of Microbiology, faculty of medicine Colombo between August 1991 to September 1992. These strains were characterized by antibiotic sensitively tests, namely-disc diffusion test heterogeneous and homogeneous resistance to methicillin; and minimum inhibitory concentration for methicillin; and other characterization tests, namely- coagulase production with human and rabbit plasma; urea hydrolysis at 24 and 48 hours; protein A levels; and pigment production